High-sensitive metal oxide gas sensor for BTEX gases based on ternary composite of CexMn1−xO2/SnO2. (26th July 2021) - Jingjing, Zhang; Zhanwu, Ning; Weijie, Liu; Peng, Zhao; Jinhua, Liu; Yanni, Zhang; Ning, Liu; Yiting, Jia; Peng, Sun
Abstract: A sensitive gas sensor based on a ternary composite of Ce x Mn1− x O2 /SnO2 was used for BTEX detection. The ternary Ce x Mn1− x O2 /SnO2 was synthesized via hydrothermal and immersion method and characterized by high resolution transmission electron microscopy and x-ray photoelectron spectroscopy. The gas sensor performances were measured on a designed flow-through microsystem consisted of a dynamic multiple gas handling unit, a test gas preheater, an olive-like test chamber and a data analysis apparatus. The developed gas sensor shows a high sensitivity towards BTEX (benzene, toluene, ethylbenzene and xylene) gases with a linear ranging from 100 to 600 ppb at optimal temperature. The sensor exhibited relative selectivity to BTEX gases compared to other VOC components. The sensing mechanism can be concluded as the 'spillover effects' of Ce x Mn1− x O2 and heterogeneous effect at the interphase of the Ce x Mn1− x O2 –SnO2 . The gas sensor developed in this paper provide a possible further application in BTEX gases, especially in ppb-level detection.